2017
DOI: 10.1101/240119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Role of the Visual Experience-Dependent Nascent Proteome in Neuronal Plasticity

Abstract: SummaryExperience-dependent synaptic plasticity refines brain circuits during development. To identify novel protein synthesis-dependent mechanisms contributing to experiencedependent plasticity, we conducted a quantitative proteomic screen of the nascent proteome in response to visual experience in Xenopus optic tectum using bio-orthogonal metabolic labeling (BONCAT). We identified 83 differentially synthesized candidate plasticity proteins (CPPs). The CPPs form strongly interconnected networks and are annota… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Chemical labeling enables enrichment of cell-surface proteins (Nunomura et al, 2005;Wollscheid et al, 2009;Zhang et al, 2003) but does not provide cell type specificity. Alternative technologies for cell-type-specific proteomics, such as bio-orthogonal metabolic labeling (Alvarez-Castelao et al, 2017;Liu et al, 2018) or organelle tagging (Fecher et al, 2019), are not amenable to analysis of cell-surface proteomes specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical labeling enables enrichment of cell-surface proteins (Nunomura et al, 2005;Wollscheid et al, 2009;Zhang et al, 2003) but does not provide cell type specificity. Alternative technologies for cell-type-specific proteomics, such as bio-orthogonal metabolic labeling (Alvarez-Castelao et al, 2017;Liu et al, 2018) or organelle tagging (Fecher et al, 2019), are not amenable to analysis of cell-surface proteomes specifically.…”
Section: Discussionmentioning
confidence: 99%
“…They usually carry an azido or alkyne functional group and can thus be immobilized on a solid phase using click chemistry and affinity purification. Although initially developed for neurobiological applications ( 95 , 96 , 97 , 98 ), the technique has since been applied to multiple systems, including primary cells ( 99 ), tissue sections ( 98 ), and in vivo in a variety of organisms, including bacteria ( 100 ), archaea ( 101 ), plants ( 102 ), zebrafish ( 97 ), and other higher eukaryotes ( 103 , 104 ). BONCAT can also be used to visualize overall proteome synthesis in cells using fluorescent non-canonical amino acid tagging ( 105 ) or to measure synthesis of target proteins in a spatially resolved manner using a proximity ligation assay ( 106 ).…”
Section: Artificial Amino Acids Using Affinity Purificationmentioning
confidence: 99%
“…Brain regions associated with pain may interact with each other during the processing of pain information [ 19 ]. In response to this view, some studies have found that the integration of excitatory neurons in S1 originates from pain information from the peripheral nerves and is transmitted to other pain-related brain regions [ 20 , 21 ]. Using the two-photon calcium ion imaging technology, it has been found that the spontaneous activity and sensory response in S1 and stimulation of S1 can increase chronic pain [ 22 ].…”
Section: Introductionmentioning
confidence: 99%